Expression of P16 in Various Grades of Oral Squamous Cell Carcinoma of Tertiary Care Hospitals of Peshawar - Karishma Ali, Sadaf Alam, Muhammad Mumtaz Khan, Natasha Kamran, Sara Zia, Shabana Bakhtiar, Sikandar Ali, Fatima Ali, Irfan Ullah; Karishma Ali, Sadaf Alam, Muhammad Mumtaz Khan, Natasha Kamran, Sara Zia, Shabana Bakhtiar, Sikandar Ali, Fatima Ali, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Oral squamous carcinoma (OSCC) is one of the ten most common carcinomas in the world. The survival rate of OSSC is poor due to its diagnosis at advanced stages, The main function of p16 in the body is to halt the tumor process, but genetic mutation may result in the development of OSCC. Objectives: The aim and objective was to compare the immunohistochemical expression of p16 in various grades of oral squamous cell carcinoma. Materials and Methods: This study was a retrospective comparative cross-sectional (Analytical) study. It was conducted at the Department of Pathology, Peshawar Medical College from August 2020 to August 2021. The sample size was calculated through G Power and 103 patients were included in the study. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) version 20.0. Chi-Square test was performed for categorical variables. Results: It was observed in our study that the mean age of OSCC was 59.16 ± 13 SD. The commonest effected age was 61-70 years (29%). The male to female ratio was approximately 1.2:1. The most common site involved by OSCC was buccal mucosa (n=49, 47%) followed by the tongue (n = 29, 29%). The p16 expression was positive in most OSCC were well differentiated (n=50, 92.5%), followed by moderately differentiated cases (n=26, 92.8%) and poorly differentiated (n=81, cases, 85.7%). There was no significant difference for p16 expression and grades of OSCC cases (P- value =0.601). Conclusion: The expression of p16 was more common in Well-differentiated oral squamous cell carcinoma, followed by moderately and poorly differentiated OSCC. Keywords: Oral Squamous cell carcinoma, P16, Human Papillomavirus